Newcastle Disease Virus Infection Interferes With the Formation of Intestinal Microflora in Newly Hatched Specific-Pathogen-Free Chicks - Cui, Ning; Huang, Xiaoying; Kong, Zhengjie; Huang, Yanyan; Huang, Qinghua; Yang, Shaohua; Zhang, Lin; Xu, Chuantian; Zhang, Xiumei; Cui, Yanshun (Frontiers in Microbiology, 2018)
Newcastle disease virus (NDV) infection leads to disproportion of intestinal tract microbiol population in chickens. Whether vertical infection of NDV affects the formation of a healthy and diverse intestinal community in newly hatched chicks, which might further perturb the establishment of a normal intestinal mucosal immunity, is unclear. This study examined the effects of NDV infection of chick embryos on the formation of the intestinal microbiome of chicks at hatch using 16S rRNA genes pyrosequencing. Eleven-day-old specific-pathogen-free chicken eggs were inoculated via intra-allantoic way with Class I NDV strain. At hatch, chicks were randomly selected and their duodenal and cecal contents were extracted and examined for the composition of gut microflora by Illumina sequencing of the V3+V4 region of the 16S rRNA genes. The results showed that the duodenal flora possesses a greater sample richness and higher microbial diversity as compared with the ceca flora in newly hatched chicks. In addition, there is a clear association with loss of important bacterial population in concert with an enrichment of potentially pathogenic population and NDV infections, both in the duodenum and ceca. It is also increasingly observed that the NDV infection may be associated with the dysbiosis of gut flora. This study presented a profile of the early intestinal microbiota in specific-pathogen-free chicks at hatch and strongly indicates that NDV infection interferes with the formation of intestinal microbiome in newly hatched chicks.